A red Roman column from Emona (Ljubljana, Slovenia) - Maver, Andreja; Županek, Bernarda; Gutman Levstik, Maja; Skaberne, Dragomir; Dolenec, Sabina (Arheološki vestnik, 2020)
The excavation conducted in 1999 in Ljubljana (Slovenia), in Insula XXVII of the Roman colonia Iulia Emona, un- earthed the remains of a column shaft with an organic core set onto a stone block. The contribution presents this find, its context and likely parallels, the mineralogical-petrographic composition of the stucco, type of the pigments used, as well as the rock of the plinth and its provenance. Of the shaft, only the stucco survives, applied in four mortar layers and painted in red ochre, while its interior surface shows the impressions of reeds. The plinth is a rectangular block made of locally available Lower Jurassic oolitic limestone, presumably from Podpeč. The column may have formed part of a porticus or peristyle, possibly associated with a pool or a bath complex in this part of Late Roman Emona.